LISTENING COMPREHENSION STUDY: DIFFICULTIES AND STRATEGIES USED BY COLLEGE STUDENTS - Dede Purwanto; Fahrus Zaman Fadhly; Wulan Rahmatunisa (Universitas Kuningan, 2021)
Listening is viewed so momentous since they are central to get a language. Listeners often do not handle listening tasks in an effective way utilizing these strategies successfully. This study investigates the listening barriers as well as listening strategies used by intermediate and upper intermediate college students. The purpose of this study are determining the listening barriers faced by those intermediate and intermediate students and presenting the listening strategies used by those intermediate and upper intermediate students in order to overcome its barriers. Within the qualitative method undertaken of this research, the result has classified the listening barriers faced by intermediate, they are: (a) accents, (b) lack of concentration, (c) speed, (d) lack of vocabularies, and (e) unclear speakers’ statement. Meanwhile, the upper intermediate’s barriers are accents and lack of vocabularies. Moreover, in order to overcome the issues, those students used several strategies that mostly for both intermediate and upper intermediate levels use these strategies, such as: (a) reading, (b) focus, (c) predicting, and (d) find the keywords. The result undertakes to increase EFL learners’ consciousness of these difficult areas in listening that are suitable and effective actions. Therefore, those EFL learners will be able to adopt several strategies in terms of listening.Keywords: listening comprehension; listening barriers; listening strategies